Describing and Analyzing Mechanical Contact for Continuum Robots Using a Shooting-Based Cosserat Rod Implementation - Wiese, Mats; Berthold, Rebecca; Wangenheim, Matthias; Raatz, Annika (IEEE robotics and automation letters, 2024)
Soft material robotic systems offer inherent safety and flexibility due to their low material stiffness. Therefore, soft material robots are prone to operate in unknown environments and fulfill tasks that involve and even exploit contact with the environment. Moving to the application of soft robots, incorporating validated contact models in modeling frameworks can be crucial for simulation tasks in, e.g. design optimization, motion planning or control. Cosserat rod models have proven themselves not only to be accurate but also computationally efficient for slender soft continuum robots (SCRs). However, only recently the topic of contact modeling has been introduced to Cosserat rod frameworks for SCRs. In this letter, for the first time we present and analyze an approach to include contact modeling in a widely used shooting-based Cosserat rod implementation. Evaluation against detailed finite element (FE) simulations indicate comparable accuracy, while the computational time remains a small fraction. Simulated data for the considered contact scenarios reveal a consistent level of agreement to experimental data, with minor discrepancies. The results are a promising basis on which further contact investigations can build.